3D Geodynamic Models for HP‐UHP Rock Exhumation in Opposite‐Dip Double Subduction‐Collision Systems. Issue 8 (29th July 2021) - Wang, Xinxin; Kaus, Boris J. P.; Yang, Jianfeng; Wang, Kun; Li, Yang; Chen, Ling; Zhao, Liang
Abstract: The dynamics of high pressure (HP) and ultra‐high pressure (UHP) rock exhumation in opposite‐dip double subduction‐collision systems remain enigmatic. Here, we present 3D thermo‐mechanical numerical models to study the geodynamics of continental‐margin subduction, collision, and crustal exhumation of HP‐UHP metamorphic rocks in oppositely dipping adjacent subduction zones. In our model setups, an initial transform‐fault separates a purely oceanic subduction zone from an adjacent oceanic subduction zone that in time transforms into continental‐margin subduction. The results show that most simulations cause continental‐margin deep subduction within the collisional belts. In contrast to the results of 2D and 3D single subduction‐collision systems, the slab‐slab interactions strongly modify the down‐channel Couette flow and the up‐channel Poiseuille flow in the interplate region when the plate edges are close to each other. This prevents the exhumation of UHP metamorphic rocks to the Earth's surface. However, far from the interplate region, rapid exhumation of UHP rocks occurs in Alpine‐type models with a low Moho temperature, strong lower crust, and fast upper‐plate divergence, whereas the Taiwan‐type models occur for a high Moho temperature, weak lower crust, fast convergence, fast erosion, and are likely to facilitate rapid dome‐like HP exhumation. Based on our results, we suggest that the main characteristics, such as deep crustal subduction and rapid exhumation of HP‐UHP metamorphic rocks during mountain building in Taiwan (∼8 Ma to present) and in the Western Alps (∼49–35 Ma), may be the result of opposite‐dip double subduction‐collision systems. Plain Language Summary: The exposure of high pressure (HP) or ultra‐high pressure (UHP) terranes is widespread in double subduction zones, but the formation mechanism of this phenomenon remains unclear. The Taiwan and Alps/Apennines orogens provide two rare opportunities to explore the physics of the formation and exhumation of HP‐UHP metamorphic rocks in two oppositely dipping adjacent subduction systems. In this study, we present 3D numerical models of how these processes occur. Our results indicate that the adjacent oceanic slab strongly changes the channel flow within the continental‐margin subduction channel in the interplate region, thereby resulting in the absence of the exhumation of UHP metamorphic rocks to the surface. The observed HP terranes in the Taiwan orogen and the HP‐UHP terranes in the Western Alps can be reproduced. These results provide important geodynamic constraints on the process of HP‐UHP rock exhumation, and we conclude that the formation and rapid exhumation of HP metamorphic rocks are associated with a high Moho temperature, weak lower crust in the continental margin, fast convergence, and fast surface erosion, whereas rapid UHP rock exhumation is facilitated by a low Moho temperature, strong lower crust, and fast upper‐plate divergence far from the interplate region. Key Points: 3D thermo‐mechanical geodynamic models to study HP‐UHP rock exhumation in opposite‐dip double subduction‐collision systems Slab interactions inhibit UHP rock exhumation in the interplate region through modifying the channel flow Crustal deformation during mountain building in Taiwan (∼8–0 Ma) and the Western Alps (∼49–35 Ma) are consistent with our simulations